Routing subject to quality of service constraints in integrated communication networks. - Lee, W.C.
With increasingly diverse QOS requirements, it is impractical to continue to rely on conventional routing paradigms that emphasize the search for an optimal path based on a predetermined metric, or a particular function of multiple metrics. Modern routing strategies must not only be adaptive to network changes but also offer considerable economy of scope. We consider the problem of routing in networks subject to QOS constraints. After providing an overview of prior routing work, we define various QOS constraints. We present a call architecture that may be used for QOS matching and a connection management mechanism for network resource allocation. We discuss fallback routing, and review some existing routing frameworks. We also present a new rule-based, call-by-call source routing strategy for integrated communication networks
Keywords: QOS matching; QOS requirements; Adaptive routing; Call architecture; Call-by-call source routing; Connection management mechanism; Fallback routing; Integrated communication networks; Network architecture; Network resource allocation; Quality of service constraints; Routing paradigms; Rule-based routing